The phenomenon of Nehru - Karunakaran, Kotta P., 1925- (Gitanjali Prakashan, 1979)
On the socio-economic, political, and foreign policy of Jawaharlal Nehru, 1889-1964; includes a representative selection of speeches and writings by Nehru and his critics.